1988
DOI: 10.1007/bf02028288
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory activity of Ebselen but not thiols in experimental alveolitis and bronchiolitis

Abstract: This paper describes the effects of the thiol compounds glutathione and N-acetylcysteine and the seleno-organic agent Ebselen on the development of Sephadex-induced lung edema and cell infiltration in the rat. Neither thiol had any effect upon the development of the edema when administered in large, repeated doses. In contrast, when Ebselen was co-administered with the thiols, there was a dose-dependent inhibition of the development of the edema, but lung weights could not be returned to normal values. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…This effect was completely inhibited in a dose-dependent fashion by ebselen with an ED50 of 4.6 mg . kg -1 and confirms previous preliminary findings [1] in which COTGREAVE et al [1] demonstrated 98% inhibition of Sephadex-induced lung oedema at a single dose of 10 mg . kg -1 .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This effect was completely inhibited in a dose-dependent fashion by ebselen with an ED50 of 4.6 mg . kg -1 and confirms previous preliminary findings [1] in which COTGREAVE et al [1] demonstrated 98% inhibition of Sephadex-induced lung oedema at a single dose of 10 mg . kg -1 .…”
Section: Discussionsupporting
confidence: 90%
“…COTGREAVE et al [1] have also demonstrated that ebselen inhibits infiltration of eosinophils, lymphocytes and basophils into the airway lumen in response to Sephadex whilst leaving the macrophage and neutrophil populations largely unchanged. This profile of biological activity would appear to be ideal for a compound targeted at treating lung inflammatory diseases as ebselen possesses the required anti-inflammatory activity whilst allowing continued protection of the lung from opportunistic infections by the presence of macrophages and neutrophils.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations